ANALYSIS OF THE INFLUENCE OF PASSENGER SATISFACTION ON SUSTAINABLE TRANSPORTATION IN THE ARCHIPELAGO REGION (BATAM - INDONESIA) - Yehezkiel Immanuel; Andri Irfan Rifai; Yusra Aulia Sari (LPPM Universitas Abdurrab, 2025)
Public transportation is vital in sustainable urban mobility by enhancing accessibility, reducing congestion, and minimising environmental impact. In Batam, Indonesia, the Trans Batam bus service is an affordable public transport option but faces challenges such as limited route coverage, inconsistent scheduling, and a lack of digital services. This study assesses passenger satisfaction with Trans Batam by evaluating key service factors, including route coverage, punctuality, cleanliness, comfort, affordability, driver attitude, safety, and overall reliability. A quantitative approach was adopted, utilising structured surveys with a 5-point Likert scale to measure satisfaction levels among 250 respondents along the Sekupang route. Results indicate improvements in cleanliness, comfort, affordability, driver attitude, and overall reliability, while route coverage and punctuality have declined due to route reductions and increasing traffic congestion. The study highlights the need for strategic improvements, such as expanding route coverage, optimizing scheduling, and leveraging digital tracking systems to enhance service quality. These findings provide valuable insights for policymakers and transport authorities to improve Batam's public transportation network and ensure long-term sustainability.